Analysis of the Development of International Tourism and Its Impact to Tourism Market: Evidence of Kazakhstan - MAKENOVA, Gulsim; TULEUBAYEVA, Meiramkul; ISSAYEVA, Akzholtay; DAURENBEKOVA, Asima (Journal of Environmental Management and Tourism, 2020)
The article examines international tourism as a part of international economic relations, its significance and dynamics over the past 5 years. Particular attention is paid to the influence of the development of the tourist market of the Republic of Kazakhstan on the materials of the Almaty region, for the optimization of which recommendations for its development are proposed. Using the provided statistical data on the development of international tourism and its impact on the development of the tourism market of the Republic of Kazakhstan on the example of the Almaty region, the analysis of the influence of some factors by means of constructing a regression model is given.